Tie-force procedure for disproportionate collapse prevention of CLT platform-type construction. (15th June 2019) - Mpidi Bita, Hercend; Tannert, Thomas
Highlights: The paper proposes indirect approach to design against disproportionate collapse. The paper presents the approach as well as its implementation at hand of a case-study building. Tie-force procedure for mid-rise CLT platform-type construction. Method uses linear-elastic static principles of engineering mechanics. Estimation of catenary and cantilever actions as collapse-resisting mechanisms. Abstract: The existing tie-force requirements for disproportionate collapse prevention, as prescribed in the current European codes and American guidelines, are unpractical for the design of Cross-laminated timber (CLT) buildings with platform-type construction. An approach towards meeting structural integrity for such buildings is presented in this paper, specifically an improved procedure to quantify the minimum longitudinal, transverse and vertical tie-force requirements. This indirect approach for disproportionate collapse prevention solely applies linear-elastic static principles of engineering mechanics to satisfy force and moment equilibriums and ensure that CLT platform-type buildings have sufficient strength, stiffness, and ductility to bridge over damaged walls. Cantilever action of the walls and catenary action of the floor panels are identified as the main collapse-resistance mechanisms. Case-study building analyses show that typical seismic design connection detailing can be used to trigger cantilever action, whereas novel connection detailing is required to meet the axial force and deformation demands required for catenary action. The procedure presented herein can aid in designing mid-rise CLT platform-type buildings for disproportionate collapse prevention.